Gender and generation perspectives in the narratives of sexually abused women in childhood - Lucimara Fabiana Fornari; Karen Namie Sakata-So; Emiko Yoshikawa Egry; Rosa Maria Godoy Serpa da Fonseca (Universidade de São Paulo, 2018)
ABSTRACT Objective: to analyze the narratives of sexually abused women in childhood, identifying issues related to gender and generation. Method: descriptive research with a qualitative approach, based on 214 reports selected from the Brazilian campaign #primeiroassedio (first harassment), which took place on Twitter social network, collected from a structured instrument. Thematic content analysis was used. Results: girls were the main victims of sexual abuse. The perpetrators were mostly male and people they knew. Five categories emerged from the narratives: Sexual abuse in the aggressors' discourse; The child as the object of sexual pleasure; Violated childhood; Victims' guilty feelings; and Repercussions of sexual abuse experienced in childhood. Conclusion: sexual abuse often occurs in the family context and, even if sometimes veiled, the submission of girls' power in gender relations and of children in generation relationships is evident. Analyzing sexual abuse under the categories of gender and generation contributes to an in-depth understanding of the phenomenon, directing practices more effectively to their coping.